The utility of the ISAC allergen array in the investigation of idiopathic anaphylaxis. (August 2014) - Heaps, A.; Carter, S.; Selwood, C.; Moody, M.; Unsworth, J.; Deacock, S.; Sumar, N.; Bansal, A.; Hayman, G.; El‐Shanawany, T.; Williams, P.; Kaminski, E.; et al.
Summary A diagnosis of idiopathic anaphylaxis following a detailed clinical assessment remains very challenging for patients and clinicians. Risk reduction strategies such as allergen avoidance are not possible. This study investigated whether the (ISAC) allergen array with 103 allergens would add diagnostic value in patients with idiopathic anaphylaxis. We extended the specific immunoglobulin (Ig)E testing in 110 patients with a diagnosis of idiopathic anaphylaxis from five UK specialist centres using ISAC arrays. These were divided into three groups: score I identified no new allergen sensitization beyond those known by previous assessment, score II identified new sensitizations which were not thought likely to explain the anaphylaxis and score III identified new sensitizations felt to have a high likelihood of being responsible for the anaphylaxis. A proportion (50%) of score III patients underwent clinical reassessment to substantiate the link to anaphylaxis in this group. The results show that 20% of the arrays were classified as score III with a high likelihood of identifying the cause of the anaphylaxis. A wide range of major allergens were identified, the most frequent being omega‐5‐gliadin and shrimp, together accounting for 45% of the previously unrecognized sensitizations. The ISAC array contributed to the diagnosis in 20% of patients with idiopathic anaphylaxis. It may offer additional information where a careful allergy history and follow‐on testing have not revealed the cause of the anaphylaxis.